Comparison of effectiveness of selected physical modalities in patients with rotator cuff injury. - Iwona Demczyszak; Natalia Kuciel; Edyta Sutkowska; Małgorzata Fortuna; Jarosław Nakiewicz (Kazimierz Wielki University, 2019)
Introduction Damage of the rotator cuff is one of the most common injuries of the shoulder in people over 50 years old and athletes. In the conservative treatment of this dysfunction the significant role has appropriately selected physical treatments. Aim of work The aim of the study was to compare the effectiveness of selected treatments of electrotherapy and cryotherapy and kinesitherapy in people with the rotator cuff damage. Materials and research method The study comprised group of 32 patients with age from 55 to 75 years, the average age - 64 years. The patients were divided randomly into two groups, A and B. Each patient performed a series of 15 treatments suggested by a specialist in accordance with current treatment methodology. In group A it were selected treatments of electrotherapy field, while in group B it were treatments of local cryotherapy and kinesitherapy. Performance evaluation was based on the visual analogue scale VAS and measuring the range of motion method SFTR. The obtained research results were statistically analyzed. Results In both treated groups reported pain reduction of 25% in group A and 51% in group B. Also observed improve and increase the mobility of the shoulder joint after performing a series of treatments. Conclusions Applied physical procedures are useful in improving people with damage to the rotator cuff. Better therapeutic effects gives the use of treatments combining cryotherapy with local kinesitherapy than using only electrotherapeutic treatments.